EUWT nowa możliwość dla współdziałania na pograniczu polsko-niemieckim - Pyrgiel, Joanna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The author describes how European Groupings of Territorial Cooperation (EGTC) operate, being a relatively new Community instrument, providing for the establishment of cooperation groups in the Community area for the purpose of facilitating and promoting territorial cooperation in order to foster economic and social cohesion. The operation of this mechanism is presented as an opportunity to develop Polish-German cooperation. In the author’s opinion, the activity of regional and local institutions located in the Polish-German borderland as concerns the issue of EGCT is rather modest, but the instrument itself is known to them, especially in the places where transborder cooperation is an element of joint activity. According to the author, the significance of EGTC as a tool is going to increase in the next support period 2014–2020 since there is a distinct European trend to take a regional attitude toward the development and implementation of EU projects.